Design and simulation of a building-based off-grid photovoltaic microgrid using PVsyst: A case study - Saikia, Anjana; Sharma, Santanu (International Journal of Electrical and Computer Engineering Systems, 2024)
In the absence of a main or central grid, an off-grid renewable energy-based system could be a viable solution to address the electricity demand of a particular region by utilizing the available renewable energy sources (RES) of that area. This also leads society to a step toward sustainable energy development. A planned RES-integrated microgrid system not only fulfills the energy crisis and reduces electricity costs but also plays a significant role in the conservation of fossil fuels. Therefore, the design and simulation of RES integrated systems are indispensable as this type of analysis determines the vital parameters of the system e.g., the system performances including electricity output, energy conversion efficiency, yearly energy potential, and the system losses before being involved in practical implementation. Further, the cell temperature of the Photovoltaic (PV) panel based on regional weather conditions, the system life cycle based on the uncertainty factor of weather, total system installation cost with a full account of the annual savings and payback etc. can also be determined by designing and simulating such systems. This paper presents a design of a 40 kW off-grid photovoltaic (PV) microgrid system according to the load requirements at the Department of Electronics and Communication Engineering (ECE), Tezpur University, India using PVsyst software. The proposed design has been created to meet the daily peak load demand of 37 kW of the department. The energy available through the generating units of the proposed designed PV system is 45.46 MWh/Year and the system performance ratio in terms of efficiency over the year is 0.814. The overall performance analysis and simulation results would be helpful in determining the efficiency and viability of the proposed PV system while implementing it practically in the near future.